A standardized analytics pipeline for reliable and rapid development and validation of prediction models using observational health data. (November 2021) - Khalid, Sara; Yang, Cynthia; Blacketer, Clair; Duarte-Salles, Talita; Fernández-Bertolín, Sergio; Kim, Chungsoo; Park, Rae Woong; Park, Jimyung; Schuemie, Martijn J.; Sena, Anthony G.; Suchard, Marc A.; You, Seng Chan; et al.
Highlights: Harmonization and quality control of originally heterogenous observational databases. Large-scale application of machine learning methods in a distributed data network. Transparent use of open-source software tools and publicly shared analytical code. Abstract: Background and objective: As a response to the ongoing COVID-19 pandemic, several prediction models in the existing literature were rapidly developed, with the aim of providing evidence-based guidance. However, none of these COVID-19 prediction models have been found to be reliable. Models are commonly assessed to have a risk of bias, often due to insufficient reporting, use of non-representative data, and lack of large-scale external validation. In this paper, we present the Observational Health Data Sciences and Informatics (OHDSI) analytics pipeline for patient-level prediction modeling as a standardized approach for rapid yet reliable development and validation of prediction models. We demonstrate how our analytics pipeline and open-source software tools can be used to answer important prediction questions while limiting potential causes of bias ( e.g., by validating phenotypes, specifying the target population, performing large-scale external validation, and publicly providing all analytical source code). Methods: We show step-by-step how to implement the analytics pipeline for the question: 'In patients hospitalized with COVID-19, what is the risk of death 0 to 30 days after hospitalization?'. We develop models using six different machine learning methods in a USA claims database containing over 20, 000 COVID-19 hospitalizations and externally validate the models using data containing over 45, 000 COVID-19 hospitalizations from South Korea, Spain, and the USA. Results: Our open-source software tools enabled us to efficiently go end-to-end from problem design to reliable Model Development and evaluation. When predicting death in patients hospitalized with COVID-19, AdaBoost, random forest, gradient boosting machine, and decision tree yielded similar or lower internal and external validation discrimination performance compared to L1-regularized logistic regression, whereas the MLP neural network consistently resulted in lower discrimination. L1-regularized logistic regression models were well calibrated. Conclusion: Our results show that following the OHDSI analytics pipeline for patient-level prediction modelling can enable the rapid development towards reliable prediction models. The OHDSI software tools and pipeline are open source and available to researchers from all around the world.